Розвиток наукових досліджень у Відділенні фізико-технічних проблем матеріалознавства НАН України - Лобанов, Л.М. (Вісник НАН України, 2019)
Статтю підготовлено за матеріалами виступу академіка-секретаря на Загальних зборах Відділення фізико-технічних проблем матеріалознавства НАН України, присвячених 100-й річниці від часу заснування Української академії наук. В історичній ретроспективі розглянуто основні етапи становлення Відділення, головні віхи у розвитку в Академії фізико-матеріалознавчого напряму науки, проаналізовано найвизначніші досягнення вчених-матеріалознавців, а також окреслено перспективи подальшого розвитку цієї наукової галузі. The article is prepared on the basis of the materials of the speech of the Academician-Secretary at the General Meeting of the Department of Physical and Technical Problems of Materials Science of NAS of Ukraine dedicated to the 100th anniversary of the foundation of the Ukrainian Academy of Sciences. In the historical retrospect, the main stages of the formation of the Department, the main milestones in the development in the Academy of physical materials science are examined, the most significant achievements of materials scientists are analyzed, and the prospects for further development of this scientific field are outlined.